2014
DOI: 10.4102/ajlm.v3i1.100
|View full text |Cite
|
Sign up to set email alerts
|

Development of a safer laboratory vervet monkey model for the study of human African trypanosomiasis

Abstract: BackgroundThere are three subspecies of Trypanosoma brucei: T. b. gambiense, T. b. rhodesiense and T. b. brucei. The first two are infectious to humans, whilst T. b. brucei is not. Identifying an animal model of T. b. brucei that mimics human African trypanosomiasis (HAT) would enable researchers to study HAT without subjecting themselves to undue risks such as accidental infection.ObjectivesThis study assessed the sequential clinical, parasitological and haematological changes in vervet monkeys infected with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
0
0
0
Order By: Relevance
“…However, an insigni cant association was recorded for animal trypanosome ITS1 DNA-positive individuals with elevated glucose, pH and protein levels. Waita et al examined urine parameters such as pH, glucose and leukocytes in vervet monkey models and observed that an elevated pH was associated with a high parasite density in monkeys 32 . Fortunately for the subjects, there were no frameshift mutations in the apoL-1 gene in the animal trypanosome ITS1 DNApositive individuals with high urine pH.…”
Section: Rate Of Positive Tests For Trypanosome Its1 Dna Detectionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, an insigni cant association was recorded for animal trypanosome ITS1 DNA-positive individuals with elevated glucose, pH and protein levels. Waita et al examined urine parameters such as pH, glucose and leukocytes in vervet monkey models and observed that an elevated pH was associated with a high parasite density in monkeys 32 . Fortunately for the subjects, there were no frameshift mutations in the apoL-1 gene in the animal trypanosome ITS1 DNApositive individuals with high urine pH.…”
Section: Rate Of Positive Tests For Trypanosome Its1 Dna Detectionmentioning
confidence: 99%
“…The research team assessed each participant to ensure that he/she met the inclusion criteria; the participant must have stayed in the community within a month and not taken anti-trypanosomal medication within that period. A total of 2 mL of venous blood and 10 mL of urine samples were collected from 240 participants (Ayekokooso (32); Kwahyia (10); Nkatenkwan (39); Santramor 1 (13) and Zorh ( 146)) for analysis.…”
Section: Samplingmentioning
confidence: 99%